2020
DOI: 10.1111/exd.14180
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane collagens—Unexplored mediators of epidermal‐dermal communication and tissue homeostasis

Abstract: Tissue homeostasis is maintained through constant, dynamic and heterogeneous communication between cells and their microenvironment. Proteins that are at the same time active at the intracellular, cell periphery and deeper extracellular levels possess the ability to, on the individual molecular level, influence the cells and their microenvironment in a bidirectional manner. The transmembrane collagens are a family of such proteins, which are of notable interest for tissue development and homeostasis. In skin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…All members of this group are also shed from the cell surface, generating soluble forms. They are found in numerous cell types and stand out for its cell adhesive properties [10,40].…”
Section: Types Of Collagens In Articular Cartilagementioning
confidence: 99%
“…All members of this group are also shed from the cell surface, generating soluble forms. They are found in numerous cell types and stand out for its cell adhesive properties [10,40].…”
Section: Types Of Collagens In Articular Cartilagementioning
confidence: 99%
“…First is the basement membrane, which provides attachment for keratinocytes and is composed of a complex network of collagen IV, nidogen, laminins and their interacting partners (reviewed in this issue by Aumailley 2 ). Transmembrane collagens extend from basal keratinocytes into the underlying dermis, forming anchoring fibrils and associated structures and are involved in providing mechanical strength as well as enabling epidermal‐dermal communication (reviewed in this issue by Nystrom and Kiritsi 3 and Watanabe et al 4 ). A large number of inherited and acquired skin diseases occur due to mutations in one of the basement membrane proteins or due to circulating autoantibodies binding to these structures 5 …”
Section: Structure Of the Skin Ecmmentioning
confidence: 99%
“…Unlike vertebrates, cephalochordates have a monolayered epidermis before, during and after regeneration, so the results of such studies would be uncomplicated by any overlying epidermal cell layers. Finally, it may well be that the molecular basis of epidermal wound repair in vertebrates—for instance, the key roles of galectins (Argüeso et al, 2015) and transmembrane collagens (Nyström & Kiritsi, 2021)—will be found to have similar functions in cephalochordates and can serve as a guide for further research.…”
Section: Discussionmentioning
confidence: 99%